PENGARUH PENDIDIKAN PANCASILA TERHADAP KARAKTER TOLERANSI SISWA KELAS VIII DI SMP NEGERI 1 SENTAJO RAYA - Okta Rinda; Hambali; Haryono (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study was motivated by the low level of tolerance of class VIII students in Junior High School Negeri 1 Sentajo Raya. To minimize this problem, there is a learning of Pancasila Education. The purpose of this study was to determine whether there is an effect of Pancasila Education on the tolerance character of class VIII students. This research uses quantitative research method with a statistical approach. The population and sample of this study were 39 students. The data analysis technique was carried out using a simple linear regression test with the help of SPSS version 27. The results showed that there was a positive and significant influence of Pancasila Education on the tolerance character of class VIII students as evidenced by the value of Fcount (10.496) ≥ Ftable (4.105). The results of the calculation of the coefficient of determination (R square) test were obtained at 22.1%, which means that there is an influence of Pancasila education on the tolerance character of class VIII students while 77.9% (100%-22.1%) is influenced by other variables not examined in this study.